Polyolefin block copolymer self-repairing material constructed by simple olefin and preparation method of polyolefin block copolymer self-repairing material

By designing polyolefin block copolymers, using olefin monomers with high melting point and low glass transition temperature, combining specific catalysts and regulating polymerization reaction conditions, the problem that polyolefin materials are difficult to self-repair under high strength and harsh environments is solved. , realizes the synthesis and application of efficient and adjustable self-repair materials.

CN119390915AActive Publication Date: 2025-02-07TIANJIN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411749684.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing polyolefin materials are difficult to achieve self-repair under high strength and harsh environments, and the synthesis process of self-repair materials is complex and have poor mechanical properties, which limits their practical application.

Method used

By designing a polyolefin block copolymer constructed from simple olefins, a first olefin monomer with a high melting point and a second olefin monomer with a low glass transition temperature are combined with a specific Group 4-6 metal complex catalyst, Co-catalyst and chain transfer agent to regulate polymerization reaction conditions to achieve efficient synthesis.

Benefits of technology

The prepared polyolefin block copolymer materials have high melting point, adjustable mechanical properties and good self-repair ability. They can self-repair under harsh conditions such as water, seawater, acids, and alkalis, extend their service life and contribute to sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390915A_ABST
    Figure CN119390915A_ABST
Patent Text Reader

Abstract

The invention discloses a polyolefin block copolymer self-repairing material constructed by simple olefin and a preparation method of the polyolefin block copolymer self-repairing material, and belongs to the technical field of polyolefin block copolymers and self-repairing materials. The mechanical property and the self-repairing property of the self-repairing material can be regulated and controlled through a combined system of the group 4-6 metal complex catalyst, the cocatalyst and the chain transfer agent with good matching property and by adjusting the structure and the proportion of each block. Wherein the homopolymerized fragment of the first olefin monomer with the high melting point provides good dimensional stability and mechanical strength for the self-repairing material, and the fragment rich in the second olefin monomer with the low glass transition temperature provides the self-repairing capability for the self-repairing material on the basis of greatly improving the tensile property and impact resistance of the self-repairing material. The obtained self-repairing material has the advantages of high melting point, adjustable mechanical properties (the elongation at break reaches 1000-2000%, and the elastic recovery rate can reach 68-98%) and good self-repairing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyolefin block copolymers and self-repairing materials, and more specifically relates to a polyolefin block copolymer self-repairing material constructed from simple olefins and a preparation method thereof. Background Art

[0002] Polymer materials have the characteristics of wide source of raw materials, light weight, easy modification and processing. They are widely used in science and technology, national defense construction and various industries of the national economy, and have become indispensable materials in all aspects of modern social life. However, it is inevitable that during processing or use, the materials will be affected by heat, mechanical force, chemical erosion, etc., forming cracks inside or on the surface. These defects seriously affect their stability, mechanical properties and service life. Traditionally, damaged materials can be repaired by welding, mechanical connection or adhesive bonding, which is not only time-consuming and labor-intensive, but also difficult to fully restore the performance of the materials. Self-healing materials developed by inspiration from biological wound healing came into being. When this material is damaged during use, no intervention is required, or only a little intervention is required, to achieve self-repair and restore the material performance. While extending the life of the material and improving safety, the maintenance cost of the material is greatly reduced, and ultimately the efficient use of resources is achieved.

[0003] To design self-healing polymer materials, it is necessary to first understand the physical and chemical processes, repair mechanisms and repair conditions involved in the material repair process. It represents the physical and chemical processes involved in the repair of polymer materials. According to the self-healing theory proposed by Wool and O'connor in J.Appl.Phys.1981,52(11),5953-5963., the physical repair steps of polymers include: (a) surface rearrangement; (b) surface approach; (c) wetting; (d) diffusion; (e) randomization process. The mutual diffusion of polymer chain segments at the damaged interface is the prerequisite for the damage recovery of polymer materials. In polymer gels or viscous liquids with low glass transition temperatures, the diffusion movement of chain segments can be easily carried out, but in polymer bulk materials with strong mechanical properties, the chain segment movement ability is generally poor, so self-healing materials with both mechanical strength are very scarce. In addition, the chemical repair process always needs to be combined with the physical repair process, because chemical reactions can only occur when the reactants are in contact with each other. After the reactive groups on both sides of the cross section contact each other through diffusion, the crack is filled by a newly formed chemical action network, so that the material recovers its original physical and mechanical properties. The most critical part of this process is the regeneration of the polymer network.

[0004] In general, the synthesis process of polymer materials with self-healing ability is often cumbersome, the structure is very complex, and the mechanical properties are poor, which greatly restricts the practical application of self-healing materials. Polyolefin materials have shown great advantages due to their wide range of low-cost raw materials and tolerance to harsh operating conditions (water, seawater, acid, and alkali). At the same time, polyolefin is the world's largest and most widely used polymer material. Realizing the self-healing of polyolefin materials is of great significance to improving resource utilization efficiency, reducing environmental pressure, and promoting sustainable development.

[0005] However, there are few reports on self-healing polyolefin materials with a single "CH" structure. This is because the simple chain structure of polyolefins often means greater versatility and environmental adaptability. At the same time, when there is a lack of chemical interactions and functional groups in the chain structure, the self-healing of the material mainly depends on the movement of the chain segments. In the case of polyolefins with a low glass transition temperature (T g ) in polymer gels or viscous liquids, the diffusion movement of chain segments can be easily carried out. However, in polymer materials with strong mechanical properties, the mobility of chain segments is usually limited, resulting in a significant decrease in self-healing efficiency and requiring an excessively long repair time. Therefore, it seems impossible to achieve self-healing properties in polyolefin materials with high strength and saturated "CH" structures. In order to break this inherent cognition, clever design is needed. Summary of the invention

[0006] The purpose of the present invention is to provide a self-healing polyolefin block copolymer material constructed from simple olefins and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art and realize the preparation of a new polyolefin block copolymer material with high melting point, adjustable mechanical properties and good self-healing properties.

[0007] To achieve the above object, the present invention provides the following solutions:

[0008] One of the technical solutions of the present invention is to provide a self-healing material of a polyolefin block copolymer constructed by simple olefins, wherein the self-healing material of the polyolefin block copolymer comprises at least one first block and at least one second block different from the first block; the first block comprises a first repeating unit, and the second block comprises a second repeating unit; the first repeating unit is polymerized by a first olefin monomer, and the second repeating unit is polymerized by a second olefin monomer; the first olefin monomer independently comprises ethylene or propylene; the second olefin monomer independently comprises butene.

[0009] Preferably, the structural formula of the polyolefin block copolymer self-healing material is as follows:

[0010]

[0011] Here, x is independently an integer ≥1, y is independently an integer ≥1, and z is independently an integer ≥1.

[0012] The second technical solution of the present invention is to provide a method for preparing the self-healing material of the polyolefin block copolymer constructed by simple olefins, comprising the following steps:

[0013] Under anhydrous and oxygen-free conditions, a first olefin monomer is introduced into a polymerization reactor equipped with a 4-6 group metal complex catalyst, a co-catalyst, a chain transfer agent and a solvent to carry out a first polymerization reaction. After the first polymerization reaction is completed, the first olefin monomer is stopped, and a second olefin monomer is introduced to carry out a second polymerization reaction. After the second polymerization reaction is completed, the first polymerization reaction and / or the second polymerization reaction are repeated n times, wherein n is an integer ≥0, to obtain the polyolefin block copolymer self-healing material;

[0014] The structural formula of the Group 4-6 metal complex catalyst is independently:

[0015] wherein M is selected from zirconium or hafnium; R1, R2 and R3 are independently selected from hydrogen, halide or C 1-8 Alkyl; Halogen includes F, Cl, Br or I; Carbon Bridge is selected from C 2-4 Alkyl, C 4-10 Cycloalkyl, Oheterocycle, Nheterocycle or Sheterocycle; G is selected from chlorine, methyl or benzyl.

[0016] The present invention can conveniently control the mechanical properties and self-healing properties of the self-healing material by combining a well-matched 4-6 group metal complex catalyst, a co-catalyst and a chain transfer agent, and adjusting the structure and proportion of each block. m The homopolymer fragment of the first olefin monomer of ) provides good dimensional stability and mechanical strength for the self-healing material, and a low glass transition temperature (T g)'s rich-second olefin monomer fragment provides self-repairing ability for self-repairing materials on the basis of greatly increasing the tensile properties and impact resistance of self-repairing materials. The prepared self-repairing material has a high melting point (131.8°C), adjustable mechanical properties (elongation at break reaches 1000-2000%, elastic recovery rate can reach 68-98%) and good self-repairing performance. The room temperature repair efficiency of the cut self-repairing material is greatly improved, and the self-repairing process can be completed in a few hours (6h). The prepared self-repairing material still has good self-repairing ability under harsh conditions such as water, seawater, acid and alkali, which greatly broadens the use scenarios. The present invention realizes the self-repairing property of polyolefin materials, which is of great significance for extending service life and promoting sustainable development. In addition, the repair material is prepared by an intermittent solution method of a single-pot reactor or a continuous solution method of a multi-pot series reactor. The preparation method is efficient, controllable, simple and easy to operate, and the raw material price is low, which provides conditions for realizing the wide application of this new type of polyolefin block copolymer self-repairing material.

[0017] In the coordination system of the Group 4-6 metal complex catalyst, the co-catalyst and the chain transfer agent described in the present invention, the Group 4-6 metal complex catalyst has excellent temperature resistance and has excellent polymerization ability for a variety of olefin monomers, playing the role of a catalytic main body, the co-catalyst can activate the catalyst and form an active center, and the chain transfer agent allows the growing molecular chain to be transferred between the active center and the chain transfer agent; the Group 4-6 metal complex catalyst, the co-catalyst and the chain transfer agent cooperate with each other to give the polymerization process a "quasi-active" feature, thereby realizing the synthesis of polyolefin block copolymers.

[0018] Preferably, the polymerization reactions are carried out in the same polymerization reactor or in m polymerization reactors connected in series; wherein, when the first polymerization reaction and the second polymerization reaction are repeated, m=2n+2; when the first polymerization reaction or the second polymerization reaction is repeated, m=n+2.

[0019] Preferably, the first olefin monomer independently comprises ethylene or propylene; and the second olefin monomer independently comprises butene.

[0020] Preferably, the cocatalyst independently comprises methylaluminoxane, modified methylaluminoxane or tetrakis(pentafluorophenyl)boride; the chain transfer agent independently comprises trialkylaluminum or dialkylzinc; the solvent independently comprises a hydrocarbon compound, and the hydrocarbon compound comprises toluene, xylene, chlorobenzene, C 6-18 Alkanes, C 6-18 Cycloalkanes or C 6-18 Mixed alkanes.

[0021] Preferably, the amount of the first olefin monomer introduced is such that the system pressure reaches 0.1 to 5 MPa; the amount of the second olefin monomer introduced is such that the system pressure reaches 0.1 to 5 MPa; and the molar ratio of the Group 4-6 metal complex catalyst, co-catalyst and chain transfer agent is independently 1:1 to 4000:50 to 800.

[0022] Preferably, the amount of the solvent used is sufficient to ensure that the materials can be dissolved so that the polymerization reaction can proceed and that the viscosity of the mixed liquid of the polymerization reaction system is moderate.

[0023] Preferably, the reaction conditions of the first polymerization reaction and the second polymerization reaction are independently: temperature 25-190° C., time 1-30 min;

[0024] The present invention can achieve the regulation of polymerization activity, polymer chain structure composition and molecular weight by controlling the temperature, pressure and time of the polymerization reaction; when the temperature of the polymerization reaction exceeds the upper limit, the catalyst will gradually be deactivated due to the high temperature; when the temperature is lower than the lower limit, the activity of the polymerization reaction is too low, and it is difficult to obtain a sufficient amount of polymer; when the pressure of the polymerization reaction exceeds the upper limit, the viscosity of the system increases, the polymerization activity is generally reduced, the insertion of the second monomer becomes difficult, and it is difficult to regulate the chain structure, thereby reducing the performance of the polymer; when the pressure is lower than the lower limit, the polymerization activity is too low, the molecular weight is reduced, and the quality of the polymer is difficult to meet the requirements; when the time of the polymerization reaction exceeds the upper limit, the system viscosity is too large, which will affect the subsequent polymerization reaction and the regulation of the chain structure; when the time is lower than the lower limit, the molecular weight of the polymer is too low, and the mechanical properties are poor.

[0025] The present invention discloses the following technical effects:

[0026] 1. The present invention adopts a combination system of a well-matched 4-6 group metal complex catalyst, a co-catalyst and a chain transfer agent, and through a single-reactor intermittent staged feeding or a multi-reactor series polymerization method, a polyolefin block copolymer self-healing material with a high melting point (131.8°C), adjustable mechanical properties (elongation at break reaches 1000-2000%, elastic recovery rate can reach 68-98%) and good self-healing properties can be obtained. High melting point (T m The homopolymer fragment of the first olefin monomer of ) provides good dimensional stability and mechanical strength for the self-healing material, and a low glass transition temperature (T g )'s second olefin-rich monomer fragment provides the self-healing material with self-healing ability on the basis of greatly increasing the tensile properties and impact resistance of the self-healing material.

[0027] 2. The present invention designs the structure of the polyolefin block copolymer self-healing material by regulating the catalyst and polymerization method, and uses the most common and readily available olefin monomers as raw materials to give self-healing properties to polyolefins with the simplest "CH" structure. The obtained polyolefin block copolymer self-healing material still has good self-healing ability under harsh conditions such as water, seawater, acid, and alkali, which greatly broadens the application scenarios.

[0028] 3. The preparation method of the present invention is efficient, controllable, simple and easy to implement, and the raw materials are inexpensive, which provides conditions for the widespread application of this new self-healing material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The high temperature gel chromatograms of the polyethylene / butene diblock copolymer in Example 1 and the polyethylene in Comparative Example 1;

[0030] Figure 2 is the polyethylene / butene diblock copolymer in Example 1 13 C-NMR spectrum;

[0031] Figure 3 is the differential scanning calorimetry (DSC) curve of the polyethylene / butene triblock copolymer in Example 2;

[0032] Figure 4 The stress-strain curve of the polypropylene / butene triblock copolymer in Example 3 after self-repair at room temperature for 6 hours after being cut;

[0033] Figure 5 This is a physical picture of the repair process of the polypropylene / butene triblock copolymer in Example 3 after self-repairing at room temperature for 6 hours after being cut;

[0034] Figure 6 The stress-strain curve of the polyethylene / butene triblock copolymer in Example 4 after self-repair in seawater for 36 hours after being cut;

[0035] Figure 7 is an atomic force microscope image of the polyethylene / butene pentablock copolymer in Example 5;

[0036] Figure 8 This is the high temperature gel chromatogram of the product obtained in Comparative Example 7. DETAILED DESCRIPTION

[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0038] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0039] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0040] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0042] Unless otherwise specified, the raw materials used in the following examples and comparative examples are all commercially available raw materials, and room temperature refers to 20-30°C;

[0043] The Group 4-6 metal complex catalysts used in the following examples and comparative examples are based on the article "Elizabeth T, Kiesewetter, ,Randoll,Madalyn,Radlauer,Robert M,Waymouth.Stereospecific octahedral group 4 bis(phenolate)ether complexes for olefin polymerization.[J].Journal of the American Chemical Society,2010,132(16):5566-7.” and “Cuthbert E N T,Vittoria A,Cipullo R,et al.Structure-Activity Relationships for Bis(phenolate-ether)Zr / Hf Propene Polymerization Catalysts[J].European Journal of Inorganic Chemistry,2020,2020(6).” and “Budzelaar M B P H M,,Alexander Z.Voskoboynikov Alexander Z.Voskoboynikov Department of Chemistry,Lomonosov Moscow State University,Moscow,Russia More by Alexander Z.Voskoboynikov,et al.The Interplay of Backbone Stiffening and Active Pocket Design in Bis(phenolate-ether)Zr / Hf Propene Polymerization Catalysts[J].ACS Catalysis,2023,13(20):13151-13155.” provided by the method.

[0044] Example 1

[0045] Under the condition of completely removing water and oxygen, xylene was used as solvent (200 mL), and a single reactor intermittent solution method strategy was adopted. Zirconium metal complex catalyst A1, modified methylaluminoxane (MMAO-7) and triisobutylaluminum were added to the reactor (ensuring that the molar ratio of zirconium metal complex catalyst A1, modified methylaluminoxane (MMAO-7) and triisobutylaluminum was 1:2000:300, and the temperature in the reactor was controlled to be 80°C, and ethylene gas was introduced into the reactor (the amount introduced was such that the system pressure reached 1MPa) for polymerization reaction, and the reaction time was 6min, and then the ethylene gas was switched to butene gas (the system pressure after introduction was 1.2MPa) to continue the second stage polymerization reaction, and the reaction time was 3min. The reaction solution obtained after the termination reaction was precipitated in acidic ethanol, filtered and dried in sequence to obtain polyethylene / butene diblock copolymer.

[0046] Wherein, the structural formula of the zirconium metal complex catalyst A1 is:

[0047]

[0048] The polyethylene / butene diblock copolymer prepared in this example was subjected to high temperature gel chromatography analysis, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the molecular weight of the block copolymer sample can reach 200 kDa and the molecular weight distribution is 2.3. 13 The results of C-NMR spectrum analysis are as follows Figure 2 As shown, from Figure 2 It can be seen that the characteristic peaks of ethylene and butene fragments coexist in the prepared product, which corresponds to the structure of polyethylene / butene diblock copolymer, indicating that the polyethylene / butene diblock copolymer was successfully synthesized.

[0049] The product obtained in Example 1 has a molar insertion ratio of ethylene to butene of 43:57 as determined by nuclear magnetic carbon spectrum; a melting point of 131.5°C, an elongation at break of 1528%, an elastic recovery rate of 75%, and a repair efficiency of 67% at 50°C for 36 hours.

[0050] Example 2

[0051] Under the condition of completely removing water and oxygen, Isopar E (produced by ExxonMobil) was used as solvent (300 mL), and a three-reactor series continuous solution method strategy was adopted. Hafnium metal complex catalyst A2, methylaluminoxane (MAO) and diethylzinc were added to the first reactor (ensuring that the molar ratio of hafnium metal complex catalyst A2, methylaluminoxane (MAO) and diethylzinc was 1:4000:100), the temperature in the first reactor was controlled to be 150°C, ethylene gas was introduced into the first reactor (the amount introduced was such that the system pressure reached 3.5 MPa) to carry out the first stage polymerization reaction, and the residence time was 10 minutes; then butene gas was introduced into the second reactor (the amount introduced was such that the system pressure reached 3.5 MPa) to continue the second stage polymerization reaction, and the residence time was 10 minutes; finally, ethylene gas was introduced into the third reactor (the amount introduced was such that the system pressure reached 3.5 MPa) to carry out the third stage polymerization, and the residence time was 20 minutes. The reaction solution obtained after the termination reaction is precipitated in acidic ethanol, filtered and dried in sequence to obtain a polyethylene / butene triblock copolymer.

[0052] Among them, the structural formula of the hafnium metal complex catalyst A2 is:

[0053]

[0054] The DSC curve of the polyethylene / butene triblock copolymer prepared in this example was analyzed, and the results were as follows: Figure 3 As shown, from Figure 3 It can be seen that the polyethylene / butene triblock copolymer has a high melting point of 131.8°C and a low glass transition temperature of -38.6°C. This high melting point and low glass transition temperature make it have the potential to be used as a self-healing material.

[0055] The product obtained in Example 2 has a molar insertion ratio of ethylene to butene of 55:45 as determined by NMR carbon spectroscopy; an elongation at break of 1634%, an elastic recovery of 68%; and a repair efficiency of 70% at 70°C for 24 hours.

[0056] Example 3

[0057] Under the condition of completely removing water and oxygen, n-hexane was used as solvent (200 mL), and a single reactor intermittent solution method strategy was adopted. Zirconium metal complex catalyst A3, tetrakis(pentafluorophenyl)borate and triethylaluminum were added to the reactor (ensuring that the molar ratio of zirconium metal complex catalyst A3, tetrakis(pentafluorophenyl)borate and triethylaluminum was 1:2.5:100), the temperature in the reactor was controlled to be 30°C, propylene gas was introduced into the reactor (the amount introduced was such that the system pressure reached 0.1MPa) to carry out the first stage polymerization reaction, and the reaction time was 5min; then propylene gas was switched to butene gas (the system pressure after introduction was 0.2MPa) to continue the second stage polymerization reaction, and the reaction time was 3min; finally, butene gas was switched to propylene gas (the system pressure after introduction was 0.2MPa) to continue the third stage polymerization, and the reaction time was 2min. The reaction solution obtained after the termination reaction was precipitated in acidic ethanol, filtered and dried in sequence to obtain polypropylene / butene triblock copolymer.

[0058] Wherein, the structural formula of the zirconium metal complex catalyst A3 is:

[0059]

[0060] The stress-strain curves of the original specimen of the polypropylene / butene triblock copolymer prepared in this example and the specimen after room temperature self-healing are shown in FIG. Figure 4 The test process is as follows: two polypropylene / butene triblock copolymers prepared in this example are melt-pressed under the same conditions to form dumbbell-shaped specimens, one of which is tested to obtain the stress-strain curve of the original specimen. The other is cut from the middle with a blade, then carefully aligned, and placed at room temperature for 6 hours before testing to obtain the stress-strain curve of the specimen after room temperature self-repair. Figure 4 It can be seen that the polypropylene / butene triblock copolymer can complete the self-repair process at room temperature for 6 hours, and the repair efficiency can reach 98%, showing excellent room temperature self-repair performance.

[0061] The actual picture of the repair process of the polypropylene / butene triblock copolymer prepared in this example is as follows Figure 5 As shown. Figure 5 It can be seen that after the repair process is completed, the traces of sample cutting completely disappear, intuitively demonstrating the excellent self-healing ability.

[0062] The product obtained in Example 3 has a molar insertion ratio of propylene to butene of 28:72 as determined by NMR carbon spectrum; a melting point of 119.8° C., an elongation at break of 1778%, and an elastic recovery rate of 95%.

[0063] Example 4

[0064] Under the condition of completely removing water and oxygen, cyclohexane was used as solvent (200 mL), and a single reactor intermittent solution method strategy was adopted. Hafnium metal complex catalyst A4, triphenyl carbon tetrakis (pentafluorophenyl) borate and trimethylaluminum were added to the reactor (ensuring that the molar ratio of hafnium metal complex catalyst A4, triphenyl carbon tetrakis (pentafluorophenyl) borate and trimethylaluminum was 1:4:400), the temperature in the reactor was controlled to be 80°C, ethylene gas was introduced into the reactor (the amount introduced was such that the system pressure reached 0.5MPa) to carry out the first stage polymerization reaction, and the reaction time was 3min; then the ethylene gas was switched to butene gas (the system pressure after introduction was 0.7MPa) to continue the second stage polymerization reaction, and the reaction time was 10min; finally, the butene gas was switched to ethylene gas (the system pressure after introduction was 1MPa) to continue the third stage polymerization, and the reaction time was 10min. The reaction solution obtained after the termination reaction was precipitated in acidic ethanol, filtered and dried in sequence to obtain polyethylene / butene triblock copolymer.

[0065] Among them, the structural formula of the hafnium metal complex catalyst A4 is:

[0066]

[0067] The stress-strain curves of the original specimen of the polyethylene / butene triblock copolymer prepared in this example and the specimen after self-repair in seawater are shown in FIG. Figure 6 The test process is as follows: two polyethylene / butene triblock copolymers prepared in this embodiment are melt-pressed under the same conditions to form dumbbell-shaped specimens, one of which is tested to obtain the stress-strain curve of the original specimen. The other is cut in the middle with a blade, then carefully aligned, and placed in seawater at 60°C for 1 hour, and then placed in seawater at 25°C for 36 hours, and the stress-strain curve of the specimen after self-repair in seawater is obtained by testing. Figure 6 It can be seen that the polyethylene / butene triblock copolymer has good mechanical properties (elongation at break is up to 1600%), and still has good self-healing ability in harsh environments such as 60°C seawater and 25°C seawater, with a repair efficiency of 91%.

[0068] The product obtained in Example 4 has a molar insertion ratio of ethylene to butene of 15:85 as determined by NMR carbon spectrum; a melting point of 129.6° C., and an elastic recovery rate of 85%.

[0069] Example 5

[0070] Under the condition of completely removing water and oxygen, toluene was used as solvent (200 mL) and a single reactor intermittent solution method strategy was adopted. Hafnium metal complex catalyst A5, N,N-dimethylaniline tetrakis (pentafluorophenyl) borate and triisobutylaluminum were added to the reactor (ensuring that the molar ratio of hafnium metal complex catalyst A5, N,N-dimethylaniline tetrakis (pentafluorophenyl) borate and triisobutylaluminum was 1:2:200), the temperature in the reactor was controlled to 50°C, ethylene gas was introduced into the reactor (the amount introduced was such that the system pressure reached 0.2 MPa) to carry out the first stage polymerization reaction, and the reaction time was 2 min; in the second stage polymerization reaction, ethylene gas was introduced into the reactor to carry out the first stage polymerization reaction. The reaction was switched to butene gas (the system pressure was 0.3MPa after the gas was introduced), and the reaction time was 3min; the third stage of the polymerization reaction was switched to ethylene gas (the system pressure was 0.4MPa after the gas was introduced), and the reaction time was 2min; the fourth stage of the polymerization reaction was switched to butene gas (the system pressure was 0.5MPa after the gas was introduced), and the reaction time was 3min; the fifth stage of the polymerization reaction was switched to ethylene gas (the system pressure was 0.6MPa after the gas was introduced), and the reaction time was 12min. The reaction solution obtained after the termination reaction was precipitated in acidic ethanol, filtered and dried in sequence to obtain a polyethylene / butene pentablock copolymer.

[0071] Among them, the structural formula of the hafnium metal complex catalyst A5 is:

[0072]

[0073] The atomic force microscope (AFM) image of the polyethylene / butene pentablock copolymer prepared in this example is as follows: Figure 7 As shown. Figure 7 It can be seen that the bright "dendritic" area is the crystal of polyethylene, the bright "lamellar" is the polybutene phase, and the dark part is the random copolymer phase. This shows that the prepared polyethylene / butene pentablock copolymer contains both polyethylene and polybutene crystalline regions and amorphous regions, and the amorphous regions are dominant. This shows that the polyethylene / butene pentablock copolymer was successfully synthesized. The presence of the random copolymer phase can serve as a low Tg "soft segment" to give the material excellent toughness and high elongation at break; on the other hand, it can improve the repair efficiency of the material.

[0074] The product obtained in Example 5 has a molar insertion ratio of ethylene to butene of 12:88 as determined by NMR carbon spectrum; a melting point of 128.4°C, an elongation at break of 1978%, and an elastic recovery rate of 97%.

[0075] Comparative Example 1

[0076] Under the condition of completely removing water and oxygen, xylene was used as solvent (200 mL) and a single reactor intermittent solution method was used to prepare the self-healing material. Zirconium metal complex catalyst A1, modified methylaluminoxane (MMAO-7) and triisobutylaluminum were added to the reactor (ensuring that the molar ratio of zirconium metal complex catalyst A1, modified methylaluminoxane (MMAO-7) and triisobutylaluminum was 1:2000:300), the temperature in the reactor was controlled to 80°C, ethylene gas was introduced into the reactor (the amount introduced was such that the system pressure reached 1MPa) for polymerization reaction, the reaction time was 6min, and after the reaction was terminated, the reaction solution was precipitated in acidic ethanol, filtered and dried in sequence to obtain polyethylene.

[0077] Wherein, the structural formula of the zirconium metal complex catalyst A1 is:

[0078]

[0079] The polyethylene / butene diblock copolymer prepared in Example 1 and the polyethylene prepared in Comparative Example 1 were subjected to high temperature gel chromatography analysis. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that the molecular weight of polyethylene is 130 kDa and the molecular weight distribution is 2.4, while the molecular weight of polyethylene / butene diblock copolymer can reach 200 kDa and the molecular weight distribution is 2.3. The molecular weight of the diblock copolymer has increased significantly compared with the homopolymer, while the molecular weight distribution remains basically unchanged, indicating that the molecular weight of the copolymer can be regulated by the polymerization time and the number of polymerization stages.

[0080] Comparative Example 2

[0081] The difference from Example 1 is that during the second stage polymerization reaction, ethylene gas is introduced at the original pressure and the same amount of butene gas as in Example 1 is introduced at the same time, and the rest is the same as in Example 1.

[0082] Performance test: The product obtained in comparative example 2 has a molar insertion ratio of ethylene:butene of 55:45 as determined by nuclear magnetic carbon spectrum; the melting point is 129.3°C; the strength decreases significantly, the elongation at break is 1766%, and the elastic recovery rate is 28%.

[0083] By comparing Example 1 with Comparative Example 2, it can be seen that the introduction of ethylene and butene gases into the second stage simultaneously increases the molar insertion rate of ethylene, but the mechanical properties decrease significantly.

[0084] Comparative Example 3

[0085] The difference from Example 2 is that during the second stage polymerization reaction, ethylene gas is introduced at the original pressure and the same amount of butene gas as in Example 2 is introduced at the same time; the rest is the same as in Example 2.

[0086] Performance test: The molar insertion ratio of ethylene to butene of the product obtained in comparative example 3 determined by nuclear magnetic carbon spectrum was 62:38; the strength decreased significantly, the elongation at break was 1565%, and the elastic recovery rate was 43%.

[0087] By comparing Example 2 with Comparative Example 3, it can be seen that the introduction of ethylene and butene gases into the second stage simultaneously increases the molar insertion rate of ethylene, but the mechanical properties decrease significantly.

[0088] Comparative Example 4

[0089] The difference from Example 3 is that during the second stage polymerization reaction, propylene gas and butene gas are introduced simultaneously, and the system pressure after the introduction is 0.2 MPa. The rest is the same as Example 3.

[0090] Performance test: The molar insertion ratio of propylene to butene of the product obtained in comparative example 4 was 35:65 as determined by nuclear magnetic carbon spectrum; the strength decreased significantly, the elongation at break was 1433%, and the elastic recovery rate was 37%.

[0091] By comparing Example 3 with Comparative Example 4, it can be seen that the introduction of propylene and butene gases simultaneously into the second stage increases the molar insertion rate of propylene, but the mechanical properties decrease significantly.

[0092] Comparative Example 5

[0093] The difference from Example 4 is that during the second stage polymerization reaction, ethylene gas and butene gas are introduced simultaneously, and the system pressure after the introduction is 0.7 MPa. The rest is the same as Example 4.

[0094] Performance test: The molar insertion ratio of ethylene to butene of the product obtained in comparative example 5 determined by nuclear magnetic carbon spectrum was 24:76; the strength decreased significantly, the elongation at break was 1268%, and there was almost no elastic recovery.

[0095] By comparing Example 4 with Comparative Example 5, it can be seen that the introduction of ethylene and butene gases into the second stage simultaneously increases the molar insertion rate of ethylene, but the mechanical properties decrease significantly.

[0096] Comparative Example 6

[0097] The difference from Example 5 is that during the second and fourth stage polymerization reactions, ethylene gas and butene gas are introduced simultaneously, and the system pressures after the introduction are 0.3 MPa and 0.5 MPa respectively. The rest is the same as Example 5.

[0098] Performance test: The molar insertion ratio of ethylene to butene of the product obtained in Comparative Example 6 was 8:92 as determined by NMR carbon spectrum; the strength decreased significantly, the elongation at break was 1421%, and there was almost no elastic recovery. The conclusion was the same as that of Comparative Example 2.

[0099] By comparing Example 5 with Comparative Example 6, it can be seen that the introduction of ethylene and butene gases into the second stage simultaneously increases the molar insertion rate of butene, but the mechanical properties decrease significantly.

[0100] Comparative Example 7

[0101] The difference from Example 1 is that the "zirconium metal complex catalyst A1" is replaced by the structural formula

[0102] The catalyst is the same as in Example 1.

[0103] The high temperature gel chromatogram of the product obtained in this comparative example is as follows Figure 8 shown.

[0104] Figure 8 The high temperature gel chromatogram of the polymer obtained in Comparative Example 7 is shown in FIG. Figure 8 It can be seen that the polymerization activity of the comparative example is very low, which is only 5 / 1 of that of Example 1. The characterization result of high temperature gel chromatography is a multimodal distribution with a molecular weight distribution of 5.8, indicating that the catalyst cannot synthesize block copolymers and the final product is a blend.

[0105] Comparative Example 8

[0106] The difference from Example 1 is that no promoter is added to the catalytic system, and the rest is the same as Example 1.

[0107] The results showed that there was no polymerization activity and no polymer could be obtained.

[0108] Comparative Example 9

[0109] The difference from Example 1 is that no chain transfer agent is added to the catalyst system, and the rest is the same as Example 1.

[0110] The results showed that the polymerization activity was reduced, the molecular weight distribution of the obtained polymer was wider (3.8), and an obvious shoulder peak appeared in the high temperature gel chromatogram, showing certain blend characteristics.

[0111] Comparative Example 10

[0112] The difference from Example 1 is that the polymerization temperature of the catalytic system is 190° C., and the rest is the same as Example 1.

[0113] The results showed that the polymerization activity increased, the molecular weight of the polymer decreased significantly, and the mechanical properties deteriorated.

[0114] Comparative Example 11

[0115] The difference from Example 1 is that the polymerization time of the first polymerization stage is 2 minutes, and the polymerization time of the second polymerization stage is 8 minutes.

[0116] The results show that the molar insertion ratio of ethylene to butene in the product obtained in comparative example 11 is 23:77, the strength decreases, the elongation at break is 1795%, the elastic recovery rate is 89%, and the self-repair efficiency is 92%. This shows that the mechanical properties and self-repair properties of the copolymer can be regulated by adjusting the polymerization time of each stage.

[0117] Comparative Example 12

[0118] The difference from Example 1 is that the introduction amount of ethylene gas and butene gas is adjusted to ensure that the pressure of the catalyst system is 8 MPa. The rest is the same as Example 1.

[0119] The results showed that: due to the excessively high reaction pressure, the viscosity of the system increased, the copolymerization activity decreased, and the ability to adjust the polymer chain structure decreased, resulting in poor comprehensive performance of the obtained polyolefin block copolymer.

[0120] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0121] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A self-healing material of a polyolefin block copolymer constructed from simple olefins, characterized in that: The polyolefin block copolymer self-healing material comprises at least one first block and at least one second block different from the first block; the first block comprises a first repeating unit, and the second block comprises a second repeating unit; the first repeating unit is polymerized from a first olefin monomer, and the second repeating unit is polymerized from a second olefin monomer; the first olefin monomer independently comprises ethylene or propylene; and the second olefin monomer independently comprises butene.

2. The method for preparing the self-healing material of polyolefin block copolymer constructed by simple olefins according to claim 1, characterized in that: The steps include: Under anhydrous and oxygen-free conditions, a first olefin monomer is introduced into a polymerization reactor equipped with a 4-6 group metal complex catalyst, a co-catalyst, a chain transfer agent and a solvent to carry out a first polymerization reaction. After the first polymerization reaction is completed, the first olefin monomer is stopped, and a second olefin monomer is introduced to carry out a second polymerization reaction. After the second polymerization reaction is completed, the first polymerization reaction and / or the second polymerization reaction are repeated n times, wherein n is an integer ≥0, to obtain the polyolefin block copolymer self-healing material; The structural formula of the Group 4-6 metal complex catalyst is independently: wherein M is selected from zirconium or hafnium; R1, R2 and R3 are independently selected from hydrogen, halide or C 1-8 Alkyl; Halogen includes F, Cl, Br or I; Carbon Bridge is selected from C 2-4 Alkyl, C 4-10 Cycloalkyl, Oheterocycle, Nheterocycle or Sheterocycle; G is selected from chlorine, methyl or benzyl.

3. The method for preparing the self-healing material of polyolefin block copolymer constructed by simple olefins according to claim 2, characterized in that: The polymerization reactions are carried out in the same polymerization reactor or in polymerization reactors connected in series.

4. The method for preparing the self-healing material of polyolefin block copolymer constructed by simple olefins according to claim 2, characterized in that: The first olefin monomer independently includes ethylene or propylene; the second olefin monomer independently includes butene.

5. The method for preparing the self-healing material of polyolefin block copolymer constructed by simple olefins according to claim 2, characterized in that: The cocatalyst independently comprises methylaluminoxane, modified methylaluminoxane or tetrakis(pentafluorophenyl)boride; and / or, the chain transfer agent independently comprises trialkylaluminum or dialkylzinc; and / or, the solvent independently comprises a hydrocarbon compound, and the hydrocarbon compound comprises toluene, xylene, chlorobenzene, C 6-18 Alkanes, C 6-18 Cycloalkanes or C 6-18 Mixed alkanes.

6. The method for preparing the self-healing material of polyolefin block copolymer constructed by simple olefins according to claim 2, characterized in that: The amount of the first olefin monomer introduced is independently such that the system pressure reaches 0.1 to 5 MPa; and / or, the amount of the second olefin monomer introduced is independently such that the system pressure reaches 0.1 to 5 MPa; and / or, the molar ratio of the Group 4-6 metal complex catalyst, the co-catalyst and the chain transfer agent is independently 1:1 to 4000:50 to 800.

7. The method for preparing the self-healing material of polyolefin block copolymer constructed by simple olefins according to claim 2, characterized in that: The reaction conditions of the first polymerization reaction and the second polymerization reaction are independently: temperature 25-190° C., time 1-30 min.

Citation Information

Patent Citations

  • A polybutene alloy material and its preparation method

    CN102268160A

  • Preparation methods of polybutylene alloy material

    CN104628912A

  • Preparation method of comb-shaped polyolefin thermoplastic elastomer based on feeding strategy regulation and control

    CN114539478A

  • Ethylene / butylene multi-block copolymer and preparation method thereof

    CN114846035A

  • Propylene and alpha-olefin multi-block copolymer elastomer material as well as preparation method and application thereof

    CN118184915A